Repair and strengthening of bamboo reinforced acrylic polymer modified square concrete columns using ferrocement jackets (2020)
This study investigated the role of acrylic polymer as concrete matrix modifier and fer- rocement jacket confinement to repair and strengthen treated bamboo reinforced square concrete columns. 30 concrete columns (CC) of 150 ×150 ×600mm were produced us- ing cement:sand:aggregate ratio of 1:3:3 and a polymer:cement ratio of 1:10 based on ACI 548.3R standard. 10 CCs’ were produced from both conventional and modified concrete which were tested until failure. Another 10 CCs’ from both concrete design mixes were preloaded at 25%, 50%, and 75% of ultimate load and thereafter repaired with ferrocement jacket and axially tested. The last 10 CCs’ were ferrocement jacketed before axial testing. Axial and lateral deflections were evaluated during the tests. The crack pattern and fail- ure modes of the columns were also considered. The highest average ultimate load was obtained from column with ferrocement and polymer addition at 60% increase in compar- ison with the control column. The least axial and lateral deflections were 93% and 72% which were from columns repaired with ferrocement material. The cracks in the interface and its propagation developed with sequential increment of load and new cracks started to form at zones closer to the upper face in contact with the machine. Bulging and peeling of mortars characterised the failure pattern of the CCs’. Acrylic polymer and ferrocement jacket repaired columns showed an improvement which came close to the strength of the unrepaired.